A Survey of Scheduling Rules - Panwalkar, S. S.; Iskander, Wafik (Operations Research, 1977)
In the past two decades researchers in the field of sequencing and scheduling have analyzed several priority dispatching rules through simulation techniques. This paper presents a summary of over 100 such rules, a list of many references that analyze them, and a classification scheme.